Detection of Mycoplasma gallisepticum in oviduct of SPF hens - Case report - Machado, Leandro dos Santos; dos Santos, Felipe Faccini; dos Santos, Lídia Maria Marques; Brandão, Mariza Dinah Manes; Gouvêa, Raquel; Abreu, Dayse Lima da Costa; Pereira, Virginia Léo de Almeida; do Nascimento, Elmiro Rosendo (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Machado L.S., Santos F.F., Santos L.M.M., BrandãoM.D.M., Abreu D.L.C., Gouvêa R., Pereira V.L.A. & Nascimento E.R. [Detection of Mycoplasma gallisepticum in oviduct of SPF hens - Case report.] Detecção de Mycoplasma gallisepticum em oviduto de galinhas SPF - Relato de caso. Revista Brasileira de Medicina Veterinária, 38(1):45-48, 2016. Faculdade de Veterinária, Universidade Federal Fluminense, Rua Vital Brasil Filho, 64, Bairro Icaraí, Niterói, RJ 24230-340, Brasil. E-mail: leomachadovet@gmail.com Mycoplasma gallisepticum (MG) has horizontal transmission, by direct contact with respiratory secretions, or vertical. Serological tests such Serum Agglutination Reaction (SAR), ELISA and PCR detection by agent are among the analyzes recommended by government programs for monitoring mycoplasmosis in poultry. This study used 40 Leghorn chickens “Specific Pathogen Free” housed in farm with historically positive by MG. The chickens were monitored monthly by SAR, ELISA, from the serum of birds and PCR from tracheal swabs. At 33 weeks old, four birds were randomly selected for analyze in the necropsy. Fragments were analyzed from different parts of the oviduct (infundibulum, magnum and isthmus) by PCR. All chickens were negative for MG to the SAR, the ELISA and PCR to 33th week of age. In the PCR, the four samples of oviduct, three were positive in the infundibulum; two in the magnum; two on the isthmus; all chickens infected with at least a portion of the oviduct. MG infection was diagnosed by PCR from the oviduct of birds which were negative by conventional monitoring techniques, prior to seroconversion by PCR and trachea swabs. Hens negative for MG using PCR from tracheal swabs and serological tests showed positive PCR results for oviduct samples.